Abnormal grain growth in (K, Na)NbO3‐based lead‐free piezoceramic powders. Issue 2 (26th September 2018) - Thong, Hao‐Cheng; Xu, Ze; Zhao, Chunlin; Lou, Lu‐Yao; Chen, Shi; Zuo, Si‐Qing; Li, Jing‐Feng; Wang, Ke
Abstract: Abnormal grain growth (AGG) is frequently observed in sintered (K, Na)NbO3 (KNN)‐based piezoceramics. However, in the present study, abnormal grain growth was unexpectedly discovered in calcined KNN‐based powders. To explain the phenomenon, three well‐established models that account for the AGG in sintered ceramics were discussed, including (a) liquid‐phase‐assisted grain growth, (b) two‐dimensional nucleation grain growth, and (c) complexion coexistence. However, the AGG in calcined powders was concluded to be none of them, but a consequence of the A‐site compositional inhomogeneity in the K2 CO3 ‐Na2 CO3 ‐Nb2 O5 ternary system. Since repeated calcination and ball milling have low efficiency on solving AGG and the accompanied compositional inhomogeneity, abnormal grains were found to coexist with normal grains at a very high calcination temperature, that is, 1000°C. The compositional inhomogeneity is believed to be remaining even after sintering and consequently deteriorate the comprehensive performances, which might be a determinant for the unstable reproduction of KNN‐based piezoceramics.